Perceived Characteristics of Intervention Scale: Development and Psychometric Properties. (December 2015) - Cook, Joan M.; Thompson, Richard; Schnurr, Paula P.
The Perceived Characteristics of Intervention Scale (PCIS), a 20-item assessment measure, was developed to assess health care providers' views of interventions. Two hundred and fifteen Department of Veterans Affairs' residential treatment providers from 38 programs across the United States completed an online survey that included the PCIS as well as self-reported use of two evidence-based treatments. The PCIS was anchored to ask about two evidence-based psychotherapies for posttraumatic stress disorder, prolonged exposure, and cognitive processing therapy. The PCIS is a reliable measure of perceived characteristics of interventions, with some preliminary support for its validity. Consideration of providers' perceptions of particular evidence-based treatments may serve as an aid to improve their dissemination, implementation, and sustained use.